Strategi Bertahan Usaha Mangkokku Pasca Pandemi Covid 19 - Setiadi , Hedi; Ambiapuri, Ema; Parwitasari, Nur Aini (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
The purpose of the study is to ascertain Mangkokku's survival strategy. Mangkokku is a restaurant that specializes in rice bowls with a touch of traditional Indonesian knowledge. Mangkokku was able to successfully adopt a survival plan during the pandemic by opening locations near residential areas, limiting their menu to takeout, and putting up a virtual kitchen. The PPKM restrictions were also implemented around this time. Mangkokku's strengths, weaknesses, opportunities, and threats are examined using a SWOT analysis. Mangkokku's company survival plan was established from the SWOT analysis in order to weather the pandemic. Qualitative research seeks to explain the complexity of the social context, investigate meaning, and get a deeper understanding of social processes. This approach is used by researchers to explain Mangkokku's post-pandemic survival strategy. A SWOT analysis reveals that Mangkokku's competitive advantages include a robust brand, innovative products, an effective supply chain, high product quality, and assured customer service. Mangkokku's shortcomings include reliance on regional markets, a lack of human resources, a small marketing budget, and a reliance on particular suppliers. Prospects in the post-pandemic Mangkokku era include e-commerce, consumer trends, market expansion, and strategic alliances. Threats to Mangkokku include fierce rivalry, alterations to laws, price swings for raw materials, and technological advancements. A plan that leverages strengths, overcomes weaknesses, seizes opportunities, and defeats threats is developed based on the SWOT analysis. Many of these actions have been taken by Mangkokku, and they can be seen as a post-pandemic survival tactic.